TVRI SUMSEL'S EFFORTS TO MAINTAIN THE EXISTENCE OF THE CHILDREN'S WORLD PROGRAM AMID THE SOCIAL MEDIA CURRENT - Lubna, Putri Piryal; Saputra, Sepriadi; Nurprameswari, Sonia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
TVRI South Sumatra's efforts to maintain the existence of the